Feasibility studies on obtaining sweet corn under winter conditions in the Baixada Fluminense - Menezes, Dinah Mochel de; Cezar, Terezinha Iza; Oliveira, Maurício Fernandes de (Pesquisa Agropecuaria Brasileira, 2014)
Plantings of the corn (Zea mays) "Seleção 47" and "Milho Doce IPEACS" were made between May and July of 1966, 1968 and 1970 at Itaguaí, Rio de Janeiro, Brazil, to study the regional possibilities of expanding sweet corn production. Plantings made in June (mid-winter) yielded better in both weight and number of ears. The cultivar Seleção 47 yielded the highest mean number and weight of ears 23,764 ears/ha and 2,409 kg/ha respectively. Productivities differences obtained between years of experimentation were highly significant. The highest means were obtained in 1966 with 28,002 ears/ha and 2,850 of ears/ha. The mean temperature (21°C) exerted influence on time number and weight of ears in the two cultivars tested. The results obtained suggested that it is feasible to expand sweet com production in the "Baixada Fluminense".